ENGLISH TITLE TRANSLATION ON IMDB OF INDONESIAN ROMANCE MOVIES RELEASED FROM 2020 TO 2024 - Raden Roro Shinta Felisia (Jurnal Sosial Humaniora dan Pendidikan, 2024)
Movie titles are also accessible through the "search filters" on IMDb. Users can input the desired title(s) in the search bar, which subsequently provides details such as the release year, runtime, IMDb rating, and a brief synopsis of the film. On IMDb, titles can also have their English version (translation or target language). Given the presence of English title translation for Indonesian movies on IMDb, the researcher believes it is important to analyze them. Among the 134 English title translation on IMDb of Indonesian romance movies released from 2020 to 2024, 20 were adapted titles and 114 were original titles. In terms of adapted titles, fully changed titles (19) were far more common than partially changed titles (1). The study identified three translation methods: literal translation (13 titles), free translation (4 titles), and a combination of free and literal translation (3 titles). These findings suggest that, in translating movie titles from Indonesian to English, the translator can face the challenge of maintaining or highlighting the significance of the original title.